Relación entre los hábitos de estudio y el rendimiento escolar de los estudiantes del 2do grado de secundaria en la I.E Divino Maestro - Naval Chavez, Segundo Enemecio (2013)
The study habits is a variable closely linked to school performance, is what highlights Santiago (2003) by stating that, "one of the most common reasons that presents on the poor performance of students at all levels of the education system is lack of study skills, such as: the proper use of time, read, make good use of what they read, how to take notes, make an outline, use good access to central information. The absence of these skills cannot set the direction and intensity of effort to define the student to obtain satisfactory achievements in their studies. lt has therefore been investigated and is still being investigated intensively on the link of these two variables in the academic world of children and young people of different ages. The research focused on the second level of secondary education of School District Divine Master Elias Vargas Soplín in order to verify the connection between these two variables as learning skills in students present. These two variables named as study habits and academic performance is studied as two components of the same process. Based on a theoreticat framework that conceptualizes and describes the habits of study as one component of the process of incorporating cognitive learning and school performance that appears induced in part by the presence of the first component with its specific characteristics as cross product of a set of academic activities. Our objective was to determine the association between study habits and academic performance in second grade students of secondary education of School District Divine Master Elias Vargas Soplín taking to 81 students as members of the population in the three existing sections in 2011. The research was adjusted to a descriptive correlational design, with the media and track inventory for examining the data, which was applied only once in both cases. The analysis and interpretation of results revolves around trends expressed as the sum of frequency in each of the indicators evaluated in the variable study habits while in school performance variable was taken into account as evaluative behavior final product of the process of learning mode supported grade qualifying expression values percentage reaching 56% on average of the three sections; also referentially had to resort to the calculation of the arithmetic mean for statistical stability test results, appreciating significant homogeneity. On the correlation was used to calculate the Pearson correlation coefficient to take the test of the hypothesis generally getting 0.88 as the coefficient r value thus failed to demonstrate that there is a positive trend as a possible association between the variables.